THE AGE OF VOLCANIC SEQUENCE IN THE MIDDLE PALEOZOIC DEPOSITS OF SOUTHERN MONGOLIA - Aristov V.A.; Nyamsuren G. (My University, 1998)
Recent finds of conodonts indicate that the volcanogenic sequence in the Gobi Altai-Suhe Bator Zone of southern Mongolia (the Gobi Altai Formation in the Dzhinsetu Ulul Range area and the Minzhin Formation in the Mandai Obo area), earlier regarded as barren of fossils, was formed in the interval between the Givetian of the Middle Devonian and the early Fammennian of the Late Devonian. The ratio of effusive and volcaniclastic rocks in the studied sections suggests that centers of volcanism moved from east to west during the indicated period.
Keywords: Paleozoic; Paleozoic; Палеозой